Fairer Futures of Work for Low-Wage Service Workers: A position statement - Dombrowski, Lynn S. (2020)
ABSTRACT I am interested in the low-wage service workers that make possible for information workers to work from home. By low-wage service workers, I mean folks who earn low-wages (low-wage typically means less than approximately 12/hour per the United States Department of Labor (USDL)) and, in some regard, work with customers (e.g., cashiers, fast food workers, retail, hospitality, warehouse, transportation, etc., all work with customers in some capacity). These low-wage folks underpin many services that make it easier, and possible to some extent, for information workers to safely stay and work from home. These services are usually embedded in sociotechnical systems that automate interactions between workers, customers, and provided services. For example, grocery and retail workers are part of sociotechnical systems that make grocery or store pick-ups possible, food and restaurant workers are part of sociotechnical systems that where food can be ordered and then automation technologies divide tasks across different workers, etc. In this position paper, I briefly discuss how low-wage service workers are a type of information worker and the ongoing relevant projects in my lab. Lastly, I will present a short Worker Centered HCI agenda for helping produce fairer futures of work. Keywords low-wage service workers; automation; IOT; economic and social justice. ABOUT THE AUTHOR/S Lynn S. Dombrowski, Ph.D. Indiana University – Purdue University lsdombro@iupui.edu Lynn S. Dombrowski is an Assistant Professor in the Human-Centered Computing Department at the School of Informatics and Computing at IUPUI. She studies, design, and prototype human-centered technologies for intervening in large systemic social issues, like social and economic inequalities (e.g., hunger; wage violations). Her work contributes to the fields of human-computer interaction, ubiquitous and social computing, and design. www.lynndombrowski.com New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).